ASUHAN KEBIDANAN CONTINUITY OF CARE PADA KASUS FISIOLOGIS DI KLINIK DAN RB EVA - Widyawati, Novia Putri (STIKES ADVAITA MEDIKA TABANAN, 2024)
The high MMR (Maternal Mortality Rate) is still a crucial matter that must be resolved by the Indonesian government. Based on data from the Ministry of Health in 2022, the number of MMR reached 4,005 and in 2023 it will increase to 4,129, making Indonesia rank second in ASEAN in terms of maternal mortality. So Continuity of Care Midwifery Care is needed which aims to provide continuous care from pregnancy to preconception so that it is able to detect any health problems experienced by clients. Care is carried out at the Eva Clinic and Maternity Home in the period November 2023 to March 2024. A series of continuous midwifery care is carried out for Mrs. I during pregnancy, childbirth, newborns, postpartum, and the decision to use contraception. After carrying out midwifery management care with a comprehensive approach and SOAP documentation, it can be seen that Mrs. I in a physiological condition at each phase of care carried out. Keywords : Continuity of Care, Midwifery Care.